The second fifty [large type] : answers to the 7 big questions of midlife and beyond - Whitman, Debra B. (Thorndike Press large print nonfiction series., 2025)
In her groundbreaking book, Debra Whitman presents practical steps we can take to help create a better second fifty for ourselves. But we can't do it alone. Whitman also calls for urgently needed changes that would make it easier for every American to enjoy a vital and meaningful second half of life. Whether you are approaching fifty, into your later years, or caring for someone who is, you'll find a wealth of wisdom in these pages. Informed by Whitman's unmatched expertise and her deep passion, The Second Fifty is an indispensable guide for living well in the twenty-first century"--